Tossing and turning: association of sleep quantity–quality with physical activity in COPD - Hirata, Raquel Pastrello (ERJ Open Res, 2020)
The association between characteristics of sleep and physical activity in daily life (PADL) has not yet been investigated in depth in subjects with COPD. This study evaluated whether time spent per day in physical activity (PA) and sedentary behaviour are associated with sleep quantity and quality in this population. Sleep and PADL were objectively assessed by an activity monitor for 7 days and analysed on a minute-by-minute basis. Subjects also underwent spirometry and 6-min walking test (6MWT). Fifty-five subjects with moderate-to-severe COPD (28 male, 67±8 years) were studied. Subjects with total time in bed (TIB) per night ≥9 h had higher wake-after-sleep onset than TIB 7–9 h and TIB ≤7 h (195 (147–218) versus 117 (75–167) and 106 (84–156) min) and more fragmented sleep than TIB ≤7 h (8.2 (6.7–14.3) versus 6.3 (5.6–6.9) sleeping bouts; p<0.05 for all). Subjects with TIB ≥9 h also spent more time per day in sedentary behaviour and less time per day in PA of light and moderate-to-vigorous intensity than those with TIB 7–9 h and ≤7 h. In multiple linear regression, TIB ≥9 h was the only significant predictor of physical inactivity (β=−3.3 (−5.1, −1.6), p≤0.0001), accounting for 20% of its variation. Sleep fragmentation was frequent and more pronounced in physically inactive than active patients (7.5 (6.3–9.6) versus 6.4 (5.5–7.3) sleeping bouts; p=0.027). In summary, subjects with COPD with TIB ≥9 h·night(−1) have more fragmented sleep, are more sedentary and less physically active than those with <9 h·night(−1), independently of the awake time. Sleep quality is frequently poor and even worse in patients classified as physically inactive.